Integration of Geospatial Data and Information in Margoluwih Village, Yogyakarta and Its Utilization for Multiple Stakeholders - Amrin, Reza Nur; Anggorowati, Dian Fitriliyani; Khoirunisa, Luluk Qoniah; Kuncoro, Dhatu Mukti; Prasetyo, Rio Aldi; Purnomo, Satya Haris; Rasendria, Alysia Delly; Meilinda, Lisa Ayu (Sekolah Tinggi Pertanahan Nasional, 2023)
As technology develops, geospatial information has been used for policy-making and decision-making. One of the geospatial technologies used is the Geographic Information System, which has been widely built and utilized by related agencies up to the village or district level. This article explains the strategy and parties involved in developing geospatial data and information integration in Margoluwih District and the benefits for these parties. The research method uses descriptive-qualitative data collection through interviews, observation, and documentation. The results of this paper show that geospatial data and information created by various parties can be integrated into an information system. The parties involved in providing data and receiving benefits from the development information system are the National Land Academy, Margoluwih District Government, Land Office of Sleman Regency, Land and Spatial Planning Office of Sleman Regency, Regional Financial and Asset Agency of Sleman Regency, UPTD Agriculture, Food, and Fisheries Extension Center Region III, Margoluwih Village Community Institution, and the Margoluwih Village Community. This indicates that the integration carried out provides benefits for multiple parties. The Margoluwih District Government, as data regent or information system manager, is expected to always maintain and update information independently and sustainably.